Lymphangioma of the Esophagus - Sae Bom Shin; Jin Il Kim; Dae Young Cheung; Yu Na Jang; Joune Seup Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Lymphangioma of the esophagus is a rare submucosal benign tumor. A 49-year-old man was referred because of a foreign body sensation in the esophagus. In endoscopy, a 10.0×1.0-cm longitudinal, translucent, whitish yellow mass covered with normal esophageal mucosa was found in the lower esophagus. Endoscopic ultrasonography revealed a heterogeneous, mainly hypoechoic, well-circum-scribed lesion located in the third layer. Incisional biopsy was performed, and histologic findings showed multiple dilated lymphatic vessels, consistent with lymphangioma. After 3 months of proton pump inhibitor treatment, the symptom was relieved and the patient is currently asymptomatic and under surveillance.